2016
DOI: 10.1007/s11130-016-0540-y
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic and Antioxidant Activity of Amaranth Hydrolysate Obtained by Activation of an Endogenous Protease

Abstract: Ingestion of diets with antithrombotic and antioxidant components offer a convenient and effective way to prevent and reduce the incidence of cardiovascular diseases. The aim of the present work was to obtain an amaranth hydrolysate by the activation of an endogenous aspartic protease, to establish adequate experimental conditions, and to evaluate its antithrombotic and antioxidant activity in order to assess its potential application as an ingredient in functional foods. The results obtained not only confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 35 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…The SDS profile showed well-defined bands with molecular weights between 57-67 kDa (Figure 1). Silva-Sánchez et al (2008), Tiengo et al (2009), Barrio & Añón (2010), Sabbione et al (2015) and Sabbione et al, (2016) revealed similar results for amaranth isolates of different cultivars.…”
Section: Resultssupporting
confidence: 61%
“…The SDS profile showed well-defined bands with molecular weights between 57-67 kDa (Figure 1). Silva-Sánchez et al (2008), Tiengo et al (2009), Barrio & Añón (2010), Sabbione et al (2015) and Sabbione et al, (2016) revealed similar results for amaranth isolates of different cultivars.…”
Section: Resultssupporting
confidence: 61%
“…Seeds and nuts have also shown to contain peptides with good antioxidant activities. Among seeds, rapeseed ( Alashi et al., 2014 ; Cumby et al., 2008 ; He et al., 2012 , 2013 ; Pan et al., 2011 ; Xue et al., 2009a , Xue et al., 2009b ; Yu et al., 2013 ; Zhang et al., 2008 , 2009 ), hemp seed ( Girgih et al., 2014 ; Girgih et al., 2013 , 2014 ; Lu et al., 2010 ), flaxseed ( Karamać et al., 2016 ; Silva et al., 2017 ), sesame ( Das et al., 2012 ; Lu et al., 2019 ; Wang et al., 2012 ), palm ( Ng et al., 2013 ; Zarei et al., 2012 , 2014 ) and amaranth seeds ( Orsini Delgado et al., 2011 ; Sabbione et al., 2016 ) are the most reported. Chia ( Silveira Coelho et al., 2019 ), pumpkin ( Venuste et al., 2013 ), watermelon ( Wen et al., 2019 ), quinoa ( Ren et al., 2017 ), perilla ( Yang et al., 2018 ), moringa ( Aderinola et al., 2019 ), sunflower ( Megías et al., 2008 ) and cassia ( Chai et al., 2019 ) have been also explored.…”
Section: Production and Identification Of Antioxidant Bioactive Peptides From Plant Biomassmentioning
confidence: 99%
“… Not identified. Sabbione et al. (2016) African Yam Bean Seed ( Sphenostylis stenocarpa ) African yam bean seed proteins Enzymatic (Alcalase) Hydrolysates and 4 fractions (UF): MW ​< ​1 ​kDa, 1 ​kDa < MW ​< ​3 ​kDa, 3 ​kDa < MW ​< ​5 ​kDa, and 5 ​kDa < MW ​< ​10 ​kDa.…”
Section: Production and Identification Of Antioxidant Bioactive Peptides From Plant Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a number of peptides with well‐established anticoagulant activity have been isolated from microbial, animal and plant sources . Hydrolyzed protein with anticoagulant activity from amaranth, peanut, pacific salmon, and Mucuna pruriens were obtained using commercial enzymes. In our laboratory, peptide fractions isolated from soluble proteins of goat cheese have also shown in vitro anticoagulant activity…”
Section: Introductionmentioning
confidence: 99%